Cybersecurity Perspectives on Protecting Intangible Commodities in the South African Financial Sector - Naidoo, Trevor (University of the Witwatersrand, Johannesburg, 2024)
The reliance on digital technologies in the financial industry has surged, elevating the value of intangible commodities like data and intellectual property. South Africa's financial sector faces escalating cyber threats, necessitating robust cybersecurity measures. This quantitative research aims to explore cybersecurity perspectives in safeguarding intangible assets within South African financial institutions. The importance of cybersecurity in safeguarding individuals and organisations from cyber threats is underscored, considering the significant financial losses and reputational damage that can result from breaches. However, challenges such as workforce shortages, skills gaps, and a lack of cybersecurity awareness persist, particularly among SMEs. The theoretical framework provides insights into individual and organisational behaviour regarding cybersecurity practices. The dissertation aimed to gather insights from technology professionals and influential leaders in cybersecurity within the financial sector of South Africa. Valuable insights into the factors influencing cybersecurity attitudes and behaviours in the South African financial sector, emphasising the importance of enforceability, subjective norms, and violation coupling in shaping attitudes towards behaviour. The study delves into key controls, monitoring effectiveness, and the feasibility of adopting global standards. By providing insights and recommendations, this research contributes to enhancing cybersecurity in South Africa's financial sector, crucial for maintaining trust, compliance, and stability in an increasingly digital world
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cybersecurity; Cyberspace; Intangible commodities; Financial Institutions; South Africa; Risk Mitigation; SDG-8: Decent work and economic growth